Topological methods for a nonlinear elliptic system with nonlinear boundary conditions - Amster, Pablo Gustavo (2009)
A nonlinear elliptic second order system with a nonlinear boundary condition is studied. We prove an existence result under a Hartman type condition. Moreover, assuming appropriate conditions of Nirenberg type, we prove the existence of solutions applying topological degree theory.